Chronological effects of atherogenic diets on the aorta, liver and spleen of rabbits. - Song, S. H. (Korean Academy of Medical Sciences, 2000)
To investigate the temporal progression of atherogenesis on the aorta and involvement of the monocyte-macrophage system in the liver and spleen, we fed 74 rabbits with high fat (14 or 7 gm%) and cholesterol (2 and 1%) diets for 4 to over 24 weeks. Using both light and electron microscopies, we found that the fibro-fatty areas on the luminal surface of aortas was spread over along the feeding time dependently. The fat deposits also in the liver and spleen worsened depending on the time of feeding the atherogenic diets. Not only monocyte-derived foam cells, but also parenchymatous cells in the liver and spleen involved become fat-laden cells. According to these results, we propose that there are three stages: 1) the primary seeding, 2) the intermediate maturing and 3) the advanced periods. These periods may play very important roles in designing the management and treatment of atherosclerotic patients.